Relações entre estrutura do habitat, composição taxonômica e trófica de peixes em riachos da bacia do rio Teles Pires, Amazônia Meridional - Cabeceira, Fernando Gonçalves (2014)
The fish fauna of tropical streams is very diversified and related to structural factors of the watercourses, but quite few is known about its happening in the northern Mato Grosso streams. My goal was to test how the fish assemblage abundance, richness and composition are related to with the streams structural variation and how the assemblage trophic groups are related to with the streams structural variation. The fishes were collected actively in stretches of 150 meters in 10 first and second order streams, in Teles Pires river basin, Cláudia-MT. Streams structural characteristics were also measured in the same sections. The species were separated into trophic groups based on stomach contents. Multivariate analyzes were performed to determine if the streams hydraulic characteristics (e.g. width, depth, flow) and substrate type influenced the distribution of species and trophic groups. The fish assemblage was composed by 24 species, which were found found from two to 11 species per stream. 317 specimens were collected, the order Characiformes was the most abundant with 43,2% of the total and eight species, followed by Siluriformes with 10 species and 37,5%, 12,9% and Gymnotiformes with two species. The fish fauna was classified into six trophic groups. The most abundant trophic group was the generalist insectivores with 123 exemplars, but the group with more species was the autochthonous insectivores with nine species. Width, depth and velocity of the streams were the most important characteristics for the structuring of fish in streams. There was a negative relationship between the composition of fish assemblages in abundance and structure of streams, which may be the result of species replacement process as well as a species addition process. However the species richness had a positive relationship with the streams structure, which can be a result of an increased number of microhabitats and the entry of species that occupy different trophic niches. Trophic analysis also revealed that the same structural features of water bodies are related to the richness of trophic groups per stream. The mass of trophic groups was not related to the streams structure. The increased size of the streams can allow the occurrence of a greater number of dominant species, opposed to the limiting effect of different species population size in small streams, strongly oligotrophic. This scenario compared to the fish assemblage structure in relation to the creeks draws attention to the necessity of forest fragments conservation where these water bodies are inserted.